Mediators for the Effect of Compassion Cultivating Training: A Longitudinal Path Analysis in a Randomized Controlled Trial Among Caregivers of People With Mental Illness - Hansen, Nanja Holland; Fjorback, Lone Overby; Frydenberg, Morten; Juul, Lise (Frontiers in Psychiatry, 2021)
Abstract Background There is a paucity of research on mediators of change, within compassion training programs. The aim was to investigate the mediators, of an eight-week compassion cultivation training (CCT) program, on the effect of psychological distress on caregivers of people with a mental illness Method Longitudinal path models in a randomized controlled trial (RCT). 192 participants were assessed for eligibility and 161 participants were included into the trial and randomized. Main outcome was psychological distress measured by Depression, Anxiety and Stress Scale at 6 months. Mediators included Self-Compassion (SC), Mindfulness (FM), and Emotion Regulation (Emotion Suppression (ES) and Cognitive Reappraisal (CR). Baseline, post, 3-and 6-month follow-up measurements were collected. Results Mediated effects for CCT; depression at 6 months: SC: -1.81 (95% CI: -3.31 to -0.31); FM: -1.98 (95% CI:-3.65 to -0.33); ER: -0.14 (95% CI:-1.31 to 1.02) ; anxiety at 6 months: SC: -0.71 (95% CI:-1.82 to 0.40); FM: -1.24 (95% CI:-2.39 to -0.09); ER: 0.18 (95% CI:-1.04 to 1.40); stress at 6 months: SC: -1.44 (95% CI:-2.84 to -0.05); FM: -2.17 (95% CI:-3.63 to -0.71); ER: -0.27 (95% CI:-1.51 to 0.98). Conclusion Mindfulness and self-compassion are important components in reducing psychological distress experienced by caregivers of people with a mental illness. Results contribute to the knowledge about the underlying mechanisms of CCT.